A New Index for Cervical Curvature Evaluation - Relative Cervical Curvature Area - Gu, Jiangpeng; Wang, Xiaoman; Xiong, Junchen; Xiao, Jun; Tian, Zirui; Liu, Xiaomin; Tian, Yu; Feng, Wei; Du, Junjie; Wang, Fei (World neurosurgery, 2024)
To put forward a new index of cervical curvature evaluation - relative cervical curvature area, and a new classification of cervical spine was proposed according to the relative cervical curvature area. A total of 167 subjects with cervical spondylosis were included in the study. Firstly, 119 subjects were selected to measure C2-C7 lordosis angle by Cobb angle method, Harrison posterior tangent method, and Jackson physiological stress line method, and then their relative cervical curvature area, C1-C7 Cobb angle, C7 slope, and T1 slope were measured. The correlation between relative cervical curvature area and 3 measurement methods and common sagittal parameters was analyzed. According to the angle classification method, we calculated the diagnostic boundary value of the relative cervical curvature area classification, and selected 48 subjects to evaluate its diagnostic efficacy. Finally, 119 subjects were re-evaluated according to the diagnostic threshold and the number of intersections to verify the feasibility of the new classification. The results showed that the relative cervical curvature area index had good intraobserver and interobserver repeatability. Relative cervical curvature area was correlated with Harrison posterior tangent method (r = 0.930), Cobb angle method (r = 0.886), and Jackson physiological stress line method (r = 0.920), and correlated with C1-C7 Cobb angle, C7 slope, and T1 slope. The relative cervical curvature area has a good diagnostic performance for distinguishing patients with lordosis, straightening, and kyphosis. According to the new classification of cervical spine, 119 subjects were divided into 57 simple lordosis, 11 simple straightening, 4 simple kyphosis, 26 S-type, and 21 RS-type. The relative cervical curvature area uses the area parameter instead of the original angle parameter and distance parameter to incorporate the change of segmental curvature, which makes up for the shortcomings of the Cobb angle method that only evaluates the curvature of 2 vertebrae, and better reflects the cervical curvature. Studies have shown that relative cervical curvature area has good repeatability and diagnostic value, and found that it has a good correlation with common cervical sagittal parameters. The new classification of cervical spine makes up for the disadvantage that the angle classification method cannot distinguish between S-type and RS-type, and initially proposes to use the number of intersections and the relative absolute value area to reflect the severity of S-type.